Statement Of Directive For Health Care Medicines Advertisement Through Indonesian Broadcast (Pragmatic Study) - Rizqon Hilmi, Muhammad; Mardikantoro, Hari Bakti; Baehaqie, Imam (Seloka: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2022)
The background of this research is the occurrence of the advertisements for health care drugs on Indonesian televisisons which contain many types of directive speech acts which have the intention to influence the community, in this case the speech partner by inviting, ordering, suggesting, and so on including the functions of inviting, ordering, asking, suggesting, challenging. This aims of this study are: (first) to find and describe the category of directive speech verbs in advertisements for health-care drugs on Indonesion television, (second) to find and describe the function of directive speech in advertisements of health-care drugs on Indonesian television, (third) to find and describe the possible effects of directiv speech for healthcare drugadvertisements on Indonesion television. The method used in this research is a descriptive method with qualitative research approach. The data of this research are the fragments of speech in advertisements for health-care drugs through Indonesian television which are supposed to be directive speech act. The data source of this research is the speech on advertisemens for health care drugs on Indonesian televisions. The results of this research are: First, three forms of directive speech verb categories used by speakers and speech partners are found - “to recomend”, “to give orders”, and “to advise”. Second, three functions of directive speech fragments on health-care drug advertisements are found on Indonesian television - suggesting, ordering and inviting. Third, two possible effects of directive speech are found, possitive effect – to make people think and to make people do something, and negative effect – the effect of making people be affraid and the effect of deceiving.